Responsabilidade tributária do sócio-administrador e a aplicabilidade do incidente de desconsideração da personalidade jurídica na execução fiscal - Nascimento, Vanessa Carrillo do (2016)
This paper aims to clarify that the tax legal relationship is closely linked to the tax obligation, when born the legal bond, which allows the active subject of this relation require a positive or negative performance of the taxpayer, and in certain situations, this obligation may be transferred to a third party, called liable, which has no direct relation to the tax legal relationship. Thus, we enter the species of tax liability provided in the tax code, and then define in the present study a only specie, which is the responsibility of a third, limited to managing partner when proven the existence of acts with excess power or violation of law, social contract or bylaws of their company. The aim is to elucidate that although the tax legislation demarcates which situations that the managing partner will be included as liable in the tax obligation it has become common that this third one is personally liable for situations not provided for in law or established in jurisprudence, the reason for which is why his defense in tax foreclosures become increasingly relevant, especially with the incident of disregard of corporate entity, provided in the Civil Procedure Code of 2015. Finally, understand that while the responsibility of the managing partner is provided for in the tax law, the application of the incident of disregard of corporate entity in tax enforcement can ward off abuses by government to require accountability of the managing partner as liable, to create opportunities for production of evidence, contradictory and full defense